Cellular and molecular mechanisms in graft-versus-host disease. Issue 2 (7th December 2015) - Zhang, Lingling; Chu, Jianhong; Yu, Jianhua; Wei, Wei
Abstract : Review of how immune cells and molecules are implicated in the physiopathology of GVHD, a complication in patients undergoing HSCT. Abstract: Graft-versus-host disease is a complication in patients undergoing hematopoietic stem cell transplantation. Graft-versus-host disease includes acute graft-versus-host disease and chronic graft-versus-host disease. Host APCs (e.g., dendritic cells and macrophages), effector T cells (e.g., Th1, Th17, and abnormal Th17:regulatory T cell ratio), B cells, and NK cells are implicated in graft-versus-host disease physiopathology. Proinflammation cytokines (e.g., IL-17, IL-1β, and TNF-α) are increased in graft-versus-host disease. Costimulatory molecules play an important role in inducing graft-versus-host disease. Pattern-recognition receptors, such as TLRs and nucleotide-binding oligomerization domain-like receptors, are critically involved in the pathogenesis of graft-versus-host disease. Complement system C3 mediates Th1/Th17 polarization in human T cell activation and skin graft-versus-host disease. Accumulation of CD26 T cells in graft-versus-host disease target organs was found. As a therapeutic target, soluble CD83 molecules or antibodies have been demonstrated to have therapeutic effects against graft-versus-host disease, and signaling molecules promote the inflammatory and immune process of graft-versus-host disease. These immune cells and molecules could be the predictors of graft-versus-host disease development and the drug targets of the treatments for graft-versus-host disease. This article focuses on major advances on cellular and molecular mechanisms in graft-versus-host disease.